Bezpieczeństwo zdrowotne — wprowadzenie do problematyki - Grzywna, Paweł (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Health security — an introduction to the problems The aim of this paper is to present and analyze the concept of health security. The main categories conditioning the health security will be explained, including the security context of the sectoral approach. Furthermore, objective and subjective aspects of health security will be taken into consideration in this paper. Key words: health security, political discourse, human security, systemic transformation